Impact of fungicide application on taro leaf blight disease in three regions of Cameroon - Manju, E.B.; Fokunang, C.N.; Mbong, G.A.; Tima, T.S.; Suh, C.; Tembe-Fokunang, E.A.; Hanna, R. (Sciencedomain International, 2017)
The study was conducted in the research field sites of the Institute of Agricultural Research (IRAD), Bambui, North West Region, (IRAD), Ekona South West Region and the International Institute of Tropical Agriculture (IITA) Nkolbisson, Yaoundé, Center Region of Cameroon. Four cultivars of taro (Dark green petiole with small leaves (L1), Red petiole with small leaves (L2), Light green petiole with large leaves (L3) and Light green petiole with small leaves(L4)) were planted in four seasons, for two years, in the months of March and July 2015, March and July 2016 in all the research farms. Ninety corms of the each cultivar were treated before planting with fungiforce at 0.33% concentration while others were not treated. Fungiforce is a contact and systemic fungicide containing high levels of copper oxide (600 grams) and mild levels of metalaxyl (120 grams), various concentrations of 0.4%, 0.33%, 0.27%, at the onset of the first symptom of leaf blight on the leaves using knapsack sprayer of 15 litres at two weeks interval, while the control experiment consisted of unsprayed taro leaves. Data for the disease incidence of taro leaf blight was recorded from the onset of disease in fields and continued at two weeks interval for 6 weeks. The results of planting taro in four seasons in three experimental field sites revealed that there was a decrease in disease incidence in fields sprayed with fungiforce than in the control field. Plots sprayed with fungicide at different concentrations showed no variation on the 4 cultivars in the different field sites. The disease incidence ranged from 10% to 100% in the 4 seasons, at the three experimental field sites. The variation in disease incidence in the three planting sites is an indication of possible genotypes by environment (GXE) interaction that may have significant influence on the taro leaf blight resistance potential.